The battle of living with obsessive compulsive disorder: a qualitative study of young people's experiences. Issue 3 (4th April 2017) - Keyes, Carly; Nolte, Lizette; Williams, Timothy I.
Abstract : Background: There has been an abundance of studies that have employed quantitative methods to research obsessive compulsive disorder (OCD) and its neurobiology and neurochemistry. However, there appears to be a paucity of research investigating how OCD is experienced by those living with the diagnosis, particularly young people. Method: A qualitative cross‐sectional semistructured interview design was used to address this lack of research. Ten young people, aged 14–17 years old, with a diagnosis of OCD were recruited from Child and Adolescent Mental Health Services in the United Kingdom. Thematic analysis was used to analyse the data. Results: Four themes were identified: 'Traumatic and stressful life events', 'Responses to signs of OCD', 'The battle of living with OCD' and 'Ambivalent relationship to help'. Young people reported experiencing stressful or traumatic life events prior to obsessive and compulsive behaviour. OCD behaviours were misunderstood by the young people and others, leading to delays in finding help. A sense of shame among the young people led them to keep their OCD secret due to feeling 'crazy'. The all‐encompassing nature of OCD led the young people to withdraw socially. Most of the young people experienced an inner conflict between fighting and giving in to the compulsions. Conclusions: Traumatic experiences may be an important factor in the development of OCD for young people, which might indicate a direction for prevention. The sense of shame and stigma needs addressing if young people are to access help earlier. Education of the public, medical professionals and educators should be a priority.